Epistemic Curiosity and Academic Self-Regulatory Learning in Undergraduates: Unveiling the Mediating Role of Academic Self-Efficacy (Journal of Asian Development Studies, 2024)
This study sought to investigate the correlation between epistemic curiosity, academic self-efficacy, and self-regulated learning in undergraduate students. The study explored how academic self-efficacy mediated the interaction between epistemic curiosity and academic self-regulating learning. Selected from many colleges in Islamabad and Rawalpindi, a suitable sample of 240 students—120 male and 120 female—aged 18 to 25 years (M=20.47, SD=1.39). The present research applied the epistemic curiosity scale (Litman, 2008), academic self-efficacy scale (Sachitra & Bandra, 2017), and the academic self-regulatory learning Questionnaire (Nambiar et al., 2022). Pearson product-moment correlation indicated a substantial positive correlation among university students' epistemic curiosity, academic self-efficacy, and academic self-regulatory learning. Using Structural Equation Modeling (SEM), mediation studies found that academic self-efficacy greatly mediated the link between epistemic curiosity and academic self-regulatory learning among university students. The results showed that undergraduate students' academic self-efficacy greatly enhanced the positive link between epistemic curiosity and academic self-regulatory learning, to maintain the positive relationship between undergraduate students' sense of epistemic curiosity and self-regulated learning, this study highlights the importance of academic self-efficacy, guiding for improving teaching strategies. It also provides empirical data to direct behavior increasing curiosity and confidence, fostering better academic performance.